Peran Media Sosial dalam Membentuk Partisipasi Politik Gen Z Pada Pemilu 2024 - Suryawijaya, Tito; Fauzy, Muhamad Rafi Nur; Maulidina, Nabila Fauziah (Jurnal Politica, 2024)
This research aims to explore the relationship between young voters, especially Generation Z (Gen Z), and political campaigns through social media in the context of the 2024 Election. Gen Z has been chosen as the subject because they are the dominant voters. This study uses a quantitative approach to understand phenomena according to the research objectives that can be measured numerically, with the population of people in Java island and using a purposive sampling technique with a sample size of 2,700 respondents of Gen Z first-time voters. This study reveals the role of social media in shaping the attitudes and political actions of Generation Z, highlighting the importance of creative and relevant campaign content in increasing theirpolitical participation. Additionally, this research also highlights that the level of political awareness, politician's image, and an understanding of important political issues are crucial in shaping the attitudes and preferences of first-time voters. This understanding provides newinsights into how social media influences the political participation of Generation Z and the importance of appropriate strategies in utilizing it.